Case Report: Midgut malrotation presenting as left-sided appendicitis with secondary omental torsion: a diagnostic challenge in a child - Yao, Han; Ma, Puneng; Gao, Ruiqi; Zhanghuang, Chenghao; Yi, Xin (Frontiers in Pediatrics, 2026)
BackgroundOmental torsion is an uncommon cause of acute abdomen in children and is usually secondary to other intra-abdominal pathology. Congenital midgut malrotation can alter anatomic relationships and lead to atypical presentations. This case report aims to highlight that congenital malrotation should be considered when left-sided appendicitis is suspected, especially when omental abnormalities are present.Case presentationWe report a 12-year-old child who presented to a tertiary children's hospital in Southwest China with more than 48 h of abdominal pain and 24 h of fever after heavy intake of indigestible meat-based snacks. Initial ultrasound showed diffuse omental thickening in the left abdomen. Repeat ultrasound revealed a hypoechoic avascular area in the perisplanic omentum, raising suspicion of omental torsion. Preoperative computed tomography demonstrated left-sided ileocecal localization consistent with midgut malrotation and features of appendicitis with localized peritonitis. Laparoscopy confirmed purulent peritonitis, a left-sided perforated appendix with abscess, and torsion of the greater omentum near the splenic pole. Appendectomy with peritoneal lavage and drainage was performed, while the omentum was managed conservatively because of gross contamination and the absence of overt necrosis. Postoperative ultrasound showed preserved omental perfusion and confirmed malrotation without volvulus. The patient recovered uneventfully and remained symptom-free during outpatient follow-up.ConclusionsWhen children present with left-sided appendicitis and omental abnormalities, congenital midgut malrotation should be considered early in the diagnostic process to optimize preoperative planning. Ultrasound is invaluable for detecting omental changes, whereas an upper gastrointestinal contrast study remains the reference test for confirming malrotation in stable patients. This case underscores the importance of close collaboration between pediatric radiologists and surgeons in managing atypical acute abdomen.